Challenges with starting vitreoretinal services in the developing world - Amissah-Arthur, Kwesi Nyan (Nepalese Journal of Ophthalmology, 2016)
Service development and improvement within ophthalmology has taken a whole new dimension with the constant improvement of equipment, and the development of therapies that significantly improve the management of our patients and as such alters their visual prognosis for the better. This improvement and increased reliance on both diagnostic and surgical equipment with the concomitant use of intravitreal therapies has arguably been felt more in the field of retinal diseases. Nepal J Ophthalmol 2016; 8(15): 1-2